Efficacy of coverage radius‐based power control scheme for interference mitigation in femtocells. Issue 8 (1st April 2014) - Kpojime, H.O.; Safdar, G.A.
Abstract : A novel coverage radius‐based downlink power control scheme to mitigate interference in densely deployed femtocells is presented. A femtocell access point (FAP) self‐update algorithm is implemented, which determines the coverage radius of the femtocell with respect to its farthest served femtocell user equipment (FUE). Based on varying coverage radii, a max/min function is used to adjust the downlink transmit power value of a FAP. System‐level simulations are performed to compare the performance of the presented scheme with the existing fixed coverage radius schemes. Even though the proposed scheme results in better cross‐tier signal to interference plus noise ratio (SINR) values, due to a low co‐tier SINR it is found that the efficacy of adaptive power control schemes based on the pilot power of a FAP is less significant if FUEs are located close to the neighbouring FAPs in densely deployed urban femtocells.